INTERNALIZATION OF CHARACTER VALUES BASED ON SPIRITUAL INTELLIGENCE AT SD ISLAM BANI HASYIM MALANG REGENCY - Muhammad Hanief; Muhammad Fahmi Hidayatullah (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2021)
SD Islam Bani Hasyim was an educational institution with a concentration on cultivating character values in students. It could be proven through heterogeneous input without selection with a quota system producing input with a diversity of learners’ intelligence and behavior. SD Islam Bani Hasyim was able to process heterogeneous input through a process based on a program-based curriculum. The program-based curriculum had relevance to the inculcation of character values in shaping spiritual intelligence was the Islamic study program and submission. This research used a descriptive qualitative approach with a case study research. The data collection technique was carried out by in-depth interviews with school leaders, participatory observation, and recorded documentation of the work of SD Islam Bani Hasyim. Analysis of research data using interactive data analysis. The research results were as follows: First, planning for value planting through understanding the institution’s philosophy, compiling relevant programs with the institutional philosophy, and socialization. Second, the implementation of value planting through Islamic programs and submission to intracurricular, extracurricular and co-curricular activities in all subjects. Third, program evaluation through open and closed surveys as well as project and product-based assignments.